Kontribusi Instrumen Moneter Syariah dan Konvensional Terhadap Inflasi di Negara OKI - Eka Puspa Dewi; Nadira Rahmandani; Sulistya Rusgianto (Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to determine the impact of Open Market Operation Sharia (OMOS), Open Market Operation Conventional (OMOC), and Interest Rates on inflation in OIC countries. This study employed a quantitative approach to the panel data technique. From 2012q2 to 2021q4, the sampled nations were Indonesia, Malaysia, Bahrain, and Pakistan. Using the Chow Test and the Hausman Test, the best models were chosen. The findings indicated that OMOS has a negative but insignificant impact on inflation. OMOC has a substantial negative impact on inflation. Consequently, interest rates have a substantial positive effect on inflation. This study can help central banks evaluate OMOS, OMOC, and interest rates to control inflation. Economic research on OMOS and inflation is limited. Researchers discovered that few previous studies discuss OMOS specifically. This study, therefore, seeks to fill in the gap.